Effects of short-duration and long-duration exercise on lipoprotein(a) - Durstine, J. L.; Davis, P. G.; Ferguson, M. A.; Alderson, N. L.; Trost, S. G. (Medicine & Science in Sports & Exercise, 2001)
PURPOSE: Most studies that use either a single exercise session, exercise training, or a cross-sectional design have failed to find a relationship between exercise and plasma lipoprotein(a) [Lp(a)] concentrations. However, a few studies investigating the effects of longer and/or more strenuous exercise have shown elevated Lp(a) concentrations, possibly as an acute-phase reactant to muscle damage. Based on the assumption that greater muscle damage would occur with exercise of longer duration, the purpose of the present study was to determine whether exercise of longer duration would increase Lp(a) concentration and creatine kinase (CK) activity more than exercise of shorter duration. METHODS: Ten endurance-trained men (mean +/- SD: age, 27 +/- 6 yr; maximal oxygen consumption [VO2max], 57 +/- 7 mL.kg-1.min-1) completed two separate exercise sessions at 70% VO2max. One session required 800 kcal of energy expenditure (60 +/- 6 min), and the other required 1500 kcal (112 +/- 12 min). Fasted blood samples were taken immediately before (0-pre), immediately after (0-post), 1 d after (1-post), and 2 d after (2-post) each exercise session. RESULTS: CK activity increased after both exercise sessions (mean +/- SE; 800 kcal: 0-pre 55 +/- 11, 1-post 168 +/- 64 U.L-1.min-1; 1500 kcal: 0-pre 51 +/- 5, 1-post 187 +/- 30, 2-post 123 +/- 19 U.L-1.min-1; P < 0.05). However, median Lp(a) concentrations were not altered by either exercise session (800 kcal: 0-pre 5.0 mg.dL-1, 0-post 3.2 mg.dL-1, 1-post 4.0 mg.dL-1, 2-post 3.4 mg.dL-1; 1500 kcal: 0-pre 5.8 mg.dL-1, 0-post 4.3 mg.dL-1, 1-post 3.2 mg.dL-1, 2-post 5.3 mg.dL-1). In addition, no relationship existed between exercise-induced changes in CK activity and Lp(a) concentration (800 kcal: r = -0.26; 1500 kcal: r = -0.02). CONCLUSION: These results suggest that plasma Lp(a) concentration will not increase in response to minor exercise-induced muscle damage in endurance-trained runners.